Glacially abraded rock flour from Greenland: Potential for macronutrient supply to plants. Issue 5 (8th August 2019) - Gunnarsen, Klara Cecilia; Jensen, Lars Stoumann; Gómez-Muñoz, Beatriz; Rosing, Minik Thorleif; de Neergaard, Andreas
Abstract: Rock flour (RF) is a fine‐grained material produced naturally by glacial movement and resulting bedrock abrasion. In Greenland fluvial transported RF from the inland ice sheet sediments in riverbeds and marine outflows. This fine‐sized RF (50% < 9.8 µm) has a high reactivity and may therefore potentially be used to rejuvenate nutrient poor soils and provide nutrients to plants. The aim of this study was to evaluate the ability of a RF from Greenland to supply P, K, Mg, and S to plants. A double‐pot system was used, in which ryegrass ( Lolium perenne L .) could take up nutrients from both a hydroponic solution and a soil‐compartment with or without RF amendment; a soil mixture or pure sand was used in the soil‐compartment to estimate RF‐soil interaction effects. Omission of single nutrients from the hydroponic solution allowed assessment of which nutrients the RF in the soil‐compartment was able to supply. Ryegrass biomass was harvested four times during 62 days. We found that RF could supply K continuously to plants grown in soil or sand, but insufficient to fully circumvent K deficiency. During 62 days 5.8% and 4.3% of the applied K from RF was accumulated in the aboveground plant tissue in soil and sand, respectively. Mg was supplied from RF to plants in sand, but no significant effects were observed in soil, possibly due to background soil Mg availability. The amounts of P and S supplied to plants were insignificant. These results indicate the potential of Greenland RF to act as a slow release K and Mg fertilizer.